Efektivitas Layanan Informasi dalam Meningkatkan Literasi Hukum Konstitusi Remaja di Lingkungan Pendidikan Formal - Iham lukman; Irham lukman (Yayasan Lentera Keadilan Cendikia, 2025)
Constitutional legal literacy serves as a fundamental pillar in shaping the character and civic awareness of adolescents. However, in practice, students’ understanding of constitutional values remains relatively low, especially amid increasingly complex social dynamics. This article aims to analyze the effectiveness of informational services within school-based Guidance and Counseling (GC) programs as an alternative approach to enhancing constitutional legal literacy in formal education settings. Employing a normative juridical method and qualitative analysis of relevant laws and academic literature, the study finds that informational services when delivered through communicative, contextual, and psycho-pedagogical approaches significantly improve students’ comprehension of their rights and responsibilities as citizens. The role of GC teachers as facilitators of legal literacy is crucial in bridging constitutional values with the realities of students’ everyday lives. Integrating informational services into GC programs strengthens the implementation of character education based on constitutional values in a holistic and sustainable manner. Thus, this non-instructional approach proves to be an effective strategy in fostering a legally literate, democratic, and socially responsible young generation.